Developing Critical Thinking in EFL Classes An Infusion Approach - Lin, Yue (Springer Singapore, 2018)
This book presents an innovative teaching experiment and an analytical study of critical thinking and the sociocultural theory of learning to illustrate the cognitive learning development mechanisms. It addresses the issues in developing critical thinking, including the controversy surrounding the definition, measurement and teaching of critical thinking, particularly in the L2 context. The book explains how infusion-thinking lessons can be structured to help students develop critical thinking along with language learning. Further, it uses a case study as a real-world example to examine the applicability and feasibility of infusion-thinking lessons in the EFL context and their effectiveness in developing students' critical thinking and language learning. Packed with thinking activities and techniques, this practical, hands-on manual provides original ideas and empirical data, giving teachers everything they need to plan their lessons to improve students' critical thinking within language courses and evaluate their teaching.